2017
DOI: 10.1021/jacs.7b08497
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactions of Phenylborylene with Dinitrogen and Carbon Monoxide

Abstract: Formal removal of two bonding partners from boranes, BR, yields borylenes, RB, which have been inferred as reactive intermediates in a number of reactions. Phenylborylene (R = CH; 1) is accessible from phenyldiazidoborane by photochemical extrusion of dinitrogen under matrix isolation conditions. Concomitantly, the nitrene PhNBN is formed via phenyl rearrangement. Here we used a combination of UV/vis, IR, and ESR spectroscopy under cryogenic matrix isolation conditions to investigate the properties and reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 47 publications
3
40
0
1
Order By: Relevance
“…108 By far, numerous transition metal-N 2 complexes taking advantage of Fe, 109a-h,j,k Mo, 109c-e,g-k W 109d,g,h have been developed for consecutive conversion of N 2 to ammonia, hydrazine and other fundamental nitrogen-containing chemicals. 109 Main-group elements supported fixation and functionalisation of N 2 is scarce, examples like borabenzene intermediate under flashthermolysis condition, 110 as well as phenyl cation 111 and phenylborylene 112 under cryogenic argon matrix condition were observed by IR spectroscopy and isotopic labelling experiments. Very recently, Braunschweig and co-workers have demonstrated that coordination of N 2 to an empty 2p-orbital of a transient borylene complex gives rise to a borylene-N 2 adduct, which either reacts with the second equivalent of borylene to afford the reductive B 2 N 2 product, 113 or is reduced by excess KC 8 to give a nitrene-like radical followed by dimerisation to afford a [N 4 ] 2À coupling product caped with two boron centres.…”
Section: Degradation Of P 4 and Asmentioning
confidence: 99%
“…108 By far, numerous transition metal-N 2 complexes taking advantage of Fe, 109a-h,j,k Mo, 109c-e,g-k W 109d,g,h have been developed for consecutive conversion of N 2 to ammonia, hydrazine and other fundamental nitrogen-containing chemicals. 109 Main-group elements supported fixation and functionalisation of N 2 is scarce, examples like borabenzene intermediate under flashthermolysis condition, 110 as well as phenyl cation 111 and phenylborylene 112 under cryogenic argon matrix condition were observed by IR spectroscopy and isotopic labelling experiments. Very recently, Braunschweig and co-workers have demonstrated that coordination of N 2 to an empty 2p-orbital of a transient borylene complex gives rise to a borylene-N 2 adduct, which either reacts with the second equivalent of borylene to afford the reductive B 2 N 2 product, 113 or is reduced by excess KC 8 to give a nitrene-like radical followed by dimerisation to afford a [N 4 ] 2À coupling product caped with two boron centres.…”
Section: Degradation Of P 4 and Asmentioning
confidence: 99%
“…1A), inspired us to test our borylene fragment as a scaffold to bind N 2 . The suitability of borylenes as candidates for N 2 binding is further underlined by a recent report of N 2 binding by the unstabilized borylene "PhB:" under matrix conditions (18).…”
mentioning
confidence: 95%
“…3,4 This suggested that borylenes might also bind N 2 , albeit using different orbitals than transition metals do (Figure B). Very recent work demonstrated binding of N 2 to an unstabilized borylene under matrix conditions at 10 K. 5 However, even at these extremely low temperatures – which are used to observe the most reactive and unstable molecules – N 2 binding was very weak. In this work, Légaré et al .…”
mentioning
confidence: 99%